ПРОБЛЕМИ ПОСТ-КІОТСЬКОЇ УГОДИ І ЗМІНИ В ЗАКОНОДАВСТВІ ВІДНОСНО СТРАТЕГІЇ ЗНИЖЕННЯ РІВНЯ ВИКИДІВ ПАРНИКОВИХ ГАЗІВ В УКРАЇНІ - Raybych, O.M. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
Negotiating process problems on drawing up of the international agreement on interactions because of the climate change after 2012 are investigated. The analysis of latest changes in the legislation on the strategy of reduction of the level of hotbed gases emission in Ukraine has been conducted. The approach to formation of the national system for regulation of hotbed gases emission under financial and economic crisis in Ukraine is offered.